Intrathecal hematoma and arachnoiditis mimicking bacterial meningitis after an epidural blood patch. (November 2017) - Roy-Gash, F.; Engrand, N.; Lecarpentier, E.; Bonnet, M.P.
Highlights: Arachnoiditis may occur after an epidural blood patch. It should be suspected if neurological signs appear after epidural blood patch. Arachnoiditis may be misdiagnosed as meningitis due to similar symptoms. The blood clot in the dural sac can be seen on a lumbar MRI. Abstract: We present a case of arachnoiditis and an intrathecal hematoma after an epidural blood patch. A 24-year-old parturient underwent an epidural blood patch three days after an accidental dural puncture during epidural labor analgesia. Four days later, the patient developed severe lower back pain, bilateral leg pain, persistent headache and fever. Bacterial meningitis was initially suspected and antibiotics started. Lumbar magnetic resonance imaging was performed and showed an intrathecal hematoma, with no blood in the epidural space. This report briefly reviews the few cases in the literature of arachnoiditis caused by an intrathecal hematoma and discusses the mechanism which resulted in blood in the subarachnoid space.